6A.03: THE RELATIONSHIP BETWEEN INTER-ARM SYSTOLIC BLOOD PRESSURE AND CARDIOVASCULAR RISK FACTORS. (June 2015) - Ma, W.; Zhang, B.; Yang, Y.; Qi, L.; Meng, L.; Zhang, Y.; Huo, Y.
Abstract : Objective: To analyze the relationship between the inter arm blood pressure difference (IASBPD) and other cardiovascular risk factors. To identify what factors are associated with this difference in a general population. Design and method: The study subjects were 1426 individuals. The BP was measured simultaneously in both arms by VP1000 vascular profiler (Omron Colin, Japan). The inter-arm BP difference was expressed as the absolute difference (|R - L|). The various risk factors, ba-PWV, carotid IMT and plaque were compared between IASBPD more than 10mmHg group and IASBPD less than 10mmHg group. The relationship between IASBPD more than 10mmHg and various cardiovascular risk factors were analyzed by multivariate logistic analysis. Results: Left upper limb systolic blood pressure was higher than the right upper limb, while right upper limb diastolic pressure was higher than the left upper limb. The prevalence of hypertension was higher in IASBPD increasing group than normal group (40.5% vs 22.6%, p < 0.05). The weight, BMI, systolic and diastolic blood pressure were also higher in IASBPD increasing group(p < 0.05). The mean IMT and max IMT in any segment carotid artery except for mean IMT of internal carotid artery were thicker in IASBPD increasing group than normal group(p < 0.05). Ba-PWV was higher, while ABI was lower in IASBPD increasing group(1.04 ± 0.16 vs 1.09 ± 0.16, p < 0.05). By multivariate logistic regression analysis, after adjusting for age, sex, BMI, hypertension, diabetes, smoking, SBP, TC, TG, LDL-C, HDL-C, ABI, PWV, mean IMT and plaque, IASBPD more than 10mmHg was positive associated with BMI(OR 1.081 95%CI: 1.030, 1.134, p = 0.002), SBP (OR 1.032 95%CI: 1.023, 1.041, p < 0.001), and negative associated with ABI(OR 0.051 95%CI: 0.009, 0.273, p = 0.001). Conclusions: The increasing IASBPD was associated with systolic blood pressure, BMI and ABI independently, which may partly explain the mechanism that increasing IASBPD is associated with cardiovascular disease.